Determination of Ni(II) in metal alloys by spectrophotometry UV-Vis using dopasemiquinone - Barreto,Wagner José (2010)
A spectrophotometric method was proposed for Ni(II) determination in alloys using a dopa-semiquinone (L-1) to form [Ni(II)(L1-)3]1-, ε = 9.3 x 10³ L mol-1 cm-1. The optimal conditions for the determination were: wavelength 590 nm, temperature 25 °C, reaction time 45 min and pH 7.5. The Beer's law was obeyed for nickel from 3.33 x 10-5 to 1.78 x 10-4 mol L-1. The method was applied to complex samples, such as inox, nickel-titanium and cobalt-chromium alloys. A study of the potential interferents revealed that Mn was the major interferent. The limit of detection and quantification were 2.88 x 10-5 mol L-1 and 3.06 x 10-5 mol L-1, respectively.